Aktualność Oświecenia według Stevena Pinkera (ze szczególnym uwzględnieniem idei postępu) - Kopciuch, Leszek (Humaniora. Czasopismo Internetowe, 2023)
In this article, I begin by sketching Steven Pinker’s understanding of main ideas of the Enlightenment, and then discuss in detail his understanding of the idea of progress. In the reconstruction section, I mainly refer to Pinker’s 2018 work Enlightenment Now: the Case for Science, Reason, Humanism, and Progress. Then I consider the issue of the relationship between Pinker’s concept of progress and the strictly philosophical understanding of this idea, clarified both in the texts of its defenders and critics.